La espada de taiji. Estilo Yang clásico - Juan Pan González (Universidad de León, 2012)
<span style="mso-ascii-font-family: Calibri; mso-fareast-font-family: Calibri; mso-hansi-font-family: Calibri; mso-bidi-font-family: 'Times New Roman'; mso-ansi-language: EN-US; mso-bidi-font-weight: bold;" lang="EN-US">Yang Jwing-Ming. <span style="mso-ascii-font-family: Calibri; mso-fareast-font-family: Calibri; mso-hansi-font-family: Calibri; mso-bidi-font-family: 'Times New Roman'; mso-ansi-language: EN-GB; mso-bidi-font-weight: bold;" lang="EN-GB">Móstoles (Madrid): Arcano Books, 2005. <span style="mso-ascii-font-family: Calibri; mso-fareast-font-family: Calibri; mso-hansi-font-family: Calibri; mso-bidi-font-family: 'Times New Roman'; mso-ansi-language: EN-US; mso-bidi-font-weight: bold;" lang="EN-US">220 páginas. 24x17 cm. I.S.B.N.: 978-84-96111-34-9.